PENGARUH PUNISHMENT TERHADAP KINERJA KARYAWAN DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN KEDAI TOKOPI PAI LI BANG DI SOCIAL MARKET PALEMBANG - Lusia Nargis; Hisbullah Basri (JURNAL KOMPETITIF, 2020)
This study basically aims to determine the effect of Punishment on Employee Performance with Work Discipline as an Intervening variable on Pai Li Bang Store employees at Social Market Palembang. From the results of data analysis conducted using path analysis it can be seen that, 1) there is a significantly positive direct effect between punishment on work discipline where tcount> ttable (3.492> 1.995) with Sig. 0.001 <0.05 and the Beta Path coefficient 0.395, which means the category of influence is strong. 2) there is a significant positive direct effect between punishment on employee performance where 2.159> 1.995 with Sig. 0.038 <0.05 and the Beta Path coefficient of 0.244 is in the medium category. 3) Then, there is a significantly positive direct effect between work discipline on employee performance where 3,591> 1,995 with Sig. 0.001 <0.05 and the Beta Path coefficient of 0.405 is categorized as strong. 4) and it is also known, that there is an indirect effect between punishment on employee performance obtained from the multiplication results between the path coefficient X to Y with the path coefficient Y to Z (0.395× 0.405) that is equal to 0.159 in the medium category. Based on the Sobel Test it is found that the value of zcount (2.4500)> ztable (1.96), the path coefficient of 0.159 is significant which means there is a mediating effect and mediation occurs in this hypothesis is a partial hypothesis, because significant punishment (X) on employee performance (Z ) did not change to be greater than 0.05 despite being influenced by mediation. Keywords: Punishment, Work Discipline, Employee Performance